Synthesis, spectral characterization and biological activities of organotin(IV) complexes heterocyclic-N4-cyclohexylthiosemicarbazone ligand - Tuan Sahikra Akmar, Binti Tuan Will (Universiti Malaysia Sarawak, UNIMAS, 2012)
The reaction of organotin(IV) chloride(s) with 2-pyridinecarboxaldehyde-N(4)-cyclohexylthiosemicarbazone [HPCCT, (1)] ligand under a nitrogen athmosphere in absolute methanol lead to the formation of seven new organotin(IV) complexes of the type [MeSnCl2(PCCT)] (2), [BuSnCl2(PCCT)] (3), [PhSnCl2(PCCT)] (4), [Me2SnCl(PCCT)] (5), [Bu2SnCl(PCCT)] (6), [Ph2SnCl(PCCT)] (7), and [Ph3Sn(PCCT)] (8). The ligand [HPCCT] (1) and its organotin(IV) complexes (2-8) were characterized by CHN analysis, molar conductivity, UV-Vis, FT-IR, and 1H NMR spectral studies. Results of spectroscopic data subjected that [HPCCT] (1) is coordinated to the tin(IV) through the thiolate-S, azomethine-N and pyridine-N atoms. Six coordinated molecular structure has been proposed for the synthesized organotin(IV) complexes. The preliminary toxicity test of ligand (1) as well as its organotin(IV) complexes (2-8) have been evaluated against Artemina Salina. Toxicity assayresults showed that the organotin(IV) complexes (2-8) exhibited better toxicity activity than free ligand.